Seasonal variation in vitamin D status, bone health and athletic performance in competitive university student athletes: a longitudinal study - Wilson-Barnes, S. L.; Hunt, J. E. A.; Williams, E. L.; Allison, S. J.; Wild, J. J.; Wainwright, J.; Lanham-New, S. A.; Manders, R. J. F. (Journal of Nutritional Science, 2020)
Vitamin D deficiency has been commonly reported in elite athletes, but the vitamin D status of UK university athletes in different training environmentsremains unknown. The present study aimed to determine any seasonal changes in vitamin D status among indoor and outdoor athletes, and whether therewas any relationship between vitamin D status and indices of physical performance and bone health. A group of forty-seven university athletes (indoor n22, outdoor n25) were tested during autumn and spring for serum vitamin D status, bone health and physical performance parameters. Blood samples wereanalysed for serum 25-hydroxyvitamin D (s-25(OH)D) status. Peak isometric knee extensor torque using an isokinetic dynamometer and jump height wasassessed using an Optojump. Aerobic capacity was estimated using the Yo-Yo intermittent recovery test. Peripheral quantitative computed tomographyscans measured radial bone mineral density. Statistical analyses were performed using appropriate parametric/non-parametric testing dependingon thenormality of the data. s-25(OH)D significantly fell between autumn (52·8(SD22·0) nmol/l) and spring (31·0(SD16·5) nmol/l;P<0·001). In spring,34 % of participants were considered to be vitamin D deficient (<25 nmol/l) according to the revised 2016 UK guidelines. These data suggest thatUK university athletes are at risk of vitamin D deficiency. Thus, further research is warranted to investigate the concomitant effects of low vitamin Dstatus on health and performance outcomes in university athletes residing at northern latitudes.